Numerical modeling and computer algorithm for the process of segregation of alloy impurities at the boundary of an oxidation wave in semiconductor substrates - Tarnavsky, G.A.; Shpak, S.I.; Obrecht, M.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2001)
An approach to the approximate modeling of complex physico-chemical processes of segregation of alloy impurities implanted in a base material is considered for the case when an oxidation wave propagates along it. A computer algorithm that realizes this approach is given. Numerical results obtained for the segregation of boron, arsenic, phosphorus, and antimony in silicon at the boundary «silicon/silicon dioxide« are discussed.